2020
DOI: 10.1021/acs.analchem.0c01628
|View full text |Cite
|
Sign up to set email alerts
|

Fully Automated Microchip Electrophoresis Analyzer for Potential Life Detection Missions

Abstract: There are a variety of complementary observations that could be used in the search for life in extraterrestrial settings. At the molecular scale, patterns in the distribution of organics could provide powerful evidence of a biotic component. In order to observe these molecular biosignatures during spaceflight missions, it is necessary to perform separation science in situ. Microchip electrophoresis (ME) is ideally suited for this task. Although this technique is readily miniaturized and numerous instruments ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 35 publications
1
50
1
Order By: Relevance
“…al. 6 created a Microchip Electrophoresis Laser-Induced Fluorescence (ME-LIF) instrument to receive a liquid sample of soil and analysed it in an automated module. This was a foundational development of microchip electrophoresis instruments for potential life-detection missions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…al. 6 created a Microchip Electrophoresis Laser-Induced Fluorescence (ME-LIF) instrument to receive a liquid sample of soil and analysed it in an automated module. This was a foundational development of microchip electrophoresis instruments for potential life-detection missions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, biomolecules are important components to test for the presence of life 2 . Studies [3][4][5][6] have revealed the efficiency of a single type of biomolecule such as protein, nucleic acid etc. as the detection method for biosignature.…”
Section: Introductionmentioning
confidence: 99%
“…MICA builds upon the Wet Chemistry Laboratory flown on the Phoenix Mars mission and employs an electrochemistry sensor array to quantitatively measure key chemical properties of Europa's surface materials and provide sample context in the search for evidence of potential biosignatures [42]. Other fluidics-based life detection instruments currently under development include Spain's Centro de Astrobiología's CMOLD (Complex Molecules Detector) and SOLID-LDChip (Signs of Life Detector-Life Detector Chip), JPL's Chemical Laptop, and UC Berkeley's EOA (Enceladus Organic Analyzer) [43][44][45][46].…”
Section: Future Technologies and Conclusionmentioning
confidence: 99%
“…Past missions on Mars have already relied on inferred measurements, using gas chromatography and mass spectrometry, and new sensors will soon be deployed. For example, an automated microchip electrophoresis analyzer mounted on a rover could detect organic biosignatures in extraterrestrial soils (Mora et al, 2020). In the far future, humans might populate some new planetary and obtain access to physical soil material, but there will always be new planetary systems to explore, so that understanding of extraterrestrial soils will always be at the limit of what the digital enables.…”
Section: Digitally Enabled Extraterrestrial Soil Sciencementioning
confidence: 99%